Production, purification and characterization of an extracellular inulinase from Kluyveromyces marxianus var. bulgaricus - Kushi, R. T.; Monti, Rubens [UNESP]; Contiero, Jonas [UNESP] (Nature America Inc, 2000)
The yeast Kluyveromyces marxianus var. bulgaricus produced large amounts of extracellular inulinase activity when grown on inulin, sucrose, fructose and glucose as carbon source, This protein has been purified to homogeneity by using successive DEAE-Trisacryl Plus and Superose 6 HR 10/30 columns. The purified enzyme showed a relative molecular weight of 57 kDa by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and 77 kDa by gel filtration in Superose 6 HR 10/30, Analysis by SDS-PAGE showed a unique polypeptide band with Coomassie Blue stain and nondenaturing PAGE of the purified enzyme obtained from media with different carbon sources showed the band, too, when stained for glucose oxidase activity, the optimal hydrolysis temperature for sucrose, raffinose and inulin was 55 degrees C and the optimal pH for sucrose was 4.75, the apparent K-m values for sucrose, raffinose and inulin are 4.58, 7.41 and 86.9 mg/ml, respectively, Thin layer chromatography showed that inulinase from K. marxianus var. bulgaricus was capable of hydrolyzing different substrates (sucrose, raffinose and inulin), releasing monosaccharides and oligosaccharides, the results obtained suggest the hypothesis that enzyme production was constitutive.
Keywords: inulin; inulinase; Kluyveromyces marxianus var. bulgaricus; extracellular enzyme